Лингвопоэтика мифологических комплексов Ф. Грильпарцера в трагедии «Золотое руно» - Даценко, Ю.В. (Культура народов Причерноморья, 2013)
В данной статье исследуется лингвопоэтика мифологических комплексов Ф.Грильпарцера
в трагедии «Золотое руно». Выявлены разные типы и формы мифологизма, характерные для
творчества Ф.Грильпарцера. Трагедия Ф. Грильпарцера рассмотрена в аспекте проблемы традиции и
новаторства в литературе. У даній статті досліджується лінгвофопоєтіка міфологічних комплексів Ф.Грільпарцера в
трагедії «Золоте руно».Своєрідність міфологізму Ф.Грільпарцера визначається оригінальною
розробкою міфологічних мотивів. Трагедія Ф.Грільпарцера розглянуто в аспекті проблеми традиції та
новаторства в літературі. In this article is researched the lingvopoetic of mythological structures by Grillparzer in his tragedy
«Gold fleece» Uniqueness of F.Grillparzer`s mythology are defined due to specific design of mythological
motive. The problem of tradition and innovation in the context of literary process is considered on the
F.Grillparzer`s tragedy. The work of Austrian writer F.Grillparzer is examined through the prism and
mytholohism mythpoetics. Various types and forms mythological characteristic of F.Grillparzer`s creativity were
found in this research. Semantics and mechanisms of mythpoetic structures were defined in the work of the
writer. The mythological role as the dominant individual style of the
writer, features and techniques mythopoetic, specific mythology of the writer are shown. Uniqueness of
F.Grillparzer`s mythology are defined due to specific design of mythological motives, themes. images and
symbols; author updating sources in accordance with the spirit of epoch; creating copyright myths. The
interaction of romantic and realistic tendencies are considered on the F. Grillparzer`s creativity.